284 Improving IT induction for paediatric staff using a live e-guide: a quality improvement project. (17th August 2022) - Kleine, Ira; Joshi, Kiran; Kerr, Maya
Abstract : Aims: Computerisation of medicine has many benefits, such as reducing prescribing errors, but unfamiliarity with IT software can make even simple day-to-day tasks challenging. St George's Hospital Paediatric Department is fully digitalised; documentation, prescribing, orders and discharge paperwork are all completed electronically. Induction to the IT system for paediatric medical staff includes online Trust-mandated induction modules and a paediatric-specific session during departmental induction. Feedback showed the departmental induction session to be poorly rated. Thus, our aim was to develop a quality improvement project focusing on the IT induction for paediatric medical staff at St George's Hospital. Methods: We conducted a survey of the new paediatric doctors starting at St Georges in September 2021 to understand their views on the current IT induction session, their initial confidence in using the hospital's IT system for daily tasks, and their suggestions for improvement of IT induction. We subsequently developed a step-by-step IT induction guide, covering all commonly-encountered aspects of the hospital IT system. The guide is a live electronic document, allowing it to be continually updated by designated people in line with the evolution of the hospital's IT systems and user feedback. This was distributed via email and WhatsApp to all junior staff, and QR code posters were displayed in doctors' offices and in the handover room. The cohort of new-starters in December 2021 were given this guide as part of their induction pack and surveyed to assess the improvement impact. Results: 12 (60%) of the September cohort completed our initial survey, and 11 (65%) of the December cohort completed the second survey. Of the initial September 2021 respondent cohort, 50% found the departmental IT induction session 'unhelpful' compared to only 9% in the December cohort, showing a 5-fold improvement after the introduction of the departmental IT Induction guide. Similarly, only 17% in the September cohort found it helpful/very helpful compared to 54% in December, showing a 3-fold improvement after the IT guide introduction. ( figure 1 ) 81% of the respondents found the new IT induction guide 'very helpful/helpful'. Conclusion: The IT induction guide was viewed as very helpful by the majority of new-starters. Overall, this project has shown that an easily-accessible step-by-step IT induction guide is a useful and easily-replicable tool to help new doctors familiarise themselves with local systems.